Peran Guru di Era Teknologi: Tantangan dan Peluang dalam Pendidikan Global - Muhammad Nasa’i Dwi Saputra; Dita Distriani; Jihan Nabilah Sholihah; Oumar Bagayoko; Afiyatun Kholifah (Pusat Riset dan Inovasi Nasional, 2024)
The rapid development of digital technology in the era of globalization has significantly transformed the field of education, particularly the role of teachers. This article aims to analyze the role of teachers in the technological era by identifying challenges and opportunities that arise in modern learning practices. The research method used is library research through the analysis of various educational literature sources such as scientific journals, educational articles, and reference books. The findings reveal that teachers in the digital era are no longer solely knowledge transmitters, but rather facilitators, learning designers, motivators, and guides in developing 21st-century skills. Opportunities include the utilization of technology as a learning medium, access to global information resources, and strengthened educational innovation. However, teachers also face challenges such as digital literacy gaps, limited technological infrastructure, technological dependency, and shifting student social values. The study concludes that strengthening teachers’ professional competence through continuous training, professional learning communities, and effective technology integration is essential in improving the quality of global education.